Feasibility and acceptability of implementing the Global Scales for Early Development (GSED) package for children 0–3 years across three countries - Ambreen Nizar Merchant; Raghbir Kaur; Gareth McCray; Vanessa Cavallera; Ann Weber; Melissa Gladstone; Magdalena Janus; Imran Nisar; Patricia Kariger; Sunil Sazawal; Arup Dutta; Salahuddin Ahmed; et al. (Pilot and Feasibility Studies)
Abstract Background To assess the neurodevelopment of children under three years, a multinational team of subject matter experts (SMEs) led by the World Health Organization (WHO) developed the Global Scales for Early Development (GSED). The measures include (1) a caregiver-reported short form (SF), (2) a directly administered long form (LF), and (3) a caregiver-reported psychosocial form (PF). The feasibility objectives of this study in Bangladesh, Pakistan, and the United Republic of Tanzania were to assess (1) the study implementation processes, including translation, training, reliability testing, and scheduling of visits and (2) the comprehensibility, cultural relevance, and acceptability of the GSED measures and the related GSED tablet-based application (app) for data collection for caregivers, children, and assessors. Methods In preparation for a large-scale validation study, we implemented several procedures to ensure that study processes were feasible during the main data collection and that the GSED was culturally appropriate, including translation and back translation of the GSED measures and country-specific training packages on study measures and procedures. Data were collected from at least 32 child-caregiver dyads, stratified by age and sex, in each country. Two methods of collecting inter-rater reliability data were tested: live in-person versus video-based assessment. Each country planned two participant visits: the first to gain consent, assess eligibility, and begin administration of the caregiver-reported GSED SF, PF, and other study measures and the second to administer the GSED LF directly to the child. Feedback on the implementation processes was evaluated by in-country assessors through focus group discussions (FGDs). Feedback on the comprehensibility, relevance, and acceptability of the GSED measures from caregivers was obtained through exit interviews in addition to the FGD of assessors. Additional cognitive interviews were conducted during administration to ensure comprehension and cultural relevance for several GSED PF items. Results The translation-back translation process identified items with words and phrases that were either mistranslated or did not have a literal matching translation in the local languages, requiring rewording or rephrasing. Implementation challenges reiterated the need to develop a more comprehensive training module covering GSED administration and other topics, including the consent process, rapport building, techniques for maintaining privacy and preventing distraction, and using didactic and interactive learning modes. Additionally, it suggested some modifications in the order of administration of measures. Assessor/supervisor concurrent scoring of assessments proved to be the most cost-effective and straightforward method for evaluating inter-rater reliability. Administration of measures using the app was considered culturally acceptable and easy to understand by most caregivers and assessors. Some mothers felt anxious about a few GSED LF items assessing motor skills. Additionally, some objects from the GSED LF kit (a set of props to test specific skills and behaviors) were unfamiliar to the children, and hence, it took extra time for them to familiarize themselves with the materials and understand the task. Conclusion This study generated invaluable information regarding the implementation of the GSED, including where improvements should be made and where the administered measures’ comprehensibility, relevance, and acceptability needed revisions. These results have implications both for the main GSED validation study and the broader assessment of children’s development in global settings, providing insights into the opportunities and challenges of assessing young children in diverse cultural settings.